The Effectiveness of the Problem-Based Learning Model Integrated STEM Approach in Improving the Critical Thinking Skills - Zulfawati, Z; Mayasari, Tantri; Handhika, Jeffry (Jurnal Penelitian Fisika dan Aplikasinya, 2022)
The research was aimed to know the effectivity of the problem-based learning with STEM approach on improving the X MIPA students’ critical thinking skills’. The research was done in SMA 1 Purwantoro. The design was one group pretest posttest design. The method of the research was a simple action research. The object of the research was X MIPA students in 2020/2021, the sample was 35 students. The technique of taking the sample was simple random sampling. The instruments were the test, the self-efficacy questionnaire, the learning response questionnaire. The result of the research showed that the problem-based learning with STEM approach was effective on improving the X MIPA students’ critical thinking skills which the result of Wilcoxon rank signed test hypothesis testing The impact of the research could develop the students critical thinking skills in order to grow a problem solver character.